ANALYSIS OF AN IMPLEMENTATION TOTAL PRODUCTIVE MAINTENANCE (TPM) USING THE OVERALL EQUIPMENT EFFECTIVENESS (OEE) METHOD ON MACHINERY PRESS CUP ROLLERAT - Denny Walady Utama; Zaharuddin Zaharuddin (INFOKUM, 2022)
PT. XZY is a company engaged in the processing of tea leaves. In carrying out the processing of tea leaves, this company uses equipment and machinery to process selected fresh teas, including a cup roller press machine. Damage to the machine or its components during an emergency can result in huge losses for the company. The purpose of this study is to implement a comprehensive maintenance program using the overall equipment effectiveness method and six big losses. From the results of the research conducted, the OEE value was obtained at 48.19% -55.92%. And the six big losses include breakdown losses 34.29%-45.38%, setup and adjustment losses 4.94%-10.73%, idle and minor stoppage losses 34.29%-45.38%, reduced speed losses 9.31% -17.87%, rework losses 0%.